Pramonės skaitmeninimas ir regioninis inovacijų efektyvumas: įrodymai iš 30 Kinijos provincijų ir miestų - Lin, Dongdong; Duan, Yu; Ma, Jingyi (Transformations In Business & Economics, 2024)
With the rapid progress of the digital technology revolution, industrial digitalization has brought new opportunities for improving regional innovation efficiency. To explore whether industrial digitalization can effectively improve regional innovation efficiency, using the panel data of 30 provinces and cities in China during 2013-2020, based on the techno-economic paradigm theory and appropriate technology theory, the influencing mechanism of industrial digitalization on regional innovation efficiency was probed into through the Super-SBM model of unexpected output, the entropy method, and the econometric analysis method. Results reveal that (1) industrial digitalization has a significantly positive impact on regional innovation efficiency in China, i.e., industrial digitalization provides a new idea for solving the dilemma of regional “innovation efficiency”. (2) Industrial digitalization indirectly improves regional innovation efficiency by optimizing the industrial structure effect and human capital effect and promoting the tendency of industrial structure and talent structure to reasonable and advanced development. (3) The innovation spillover of industrial digitalization exhibits double threshold effects. The threshold value in Central China is the minimum and the highest growth rate is observed in Western China, providing an opportunity window for the central and western regions to realize corner overtaking. In this study, the influencing process and action conditions of industrial digitalization on regional innovation efficiency were revealed and the application scenarios of digital technological innovation were expanded, providing a reference for China to implement digital transformation and formulate innovation strategies.